Biparental contributions of the H2A.B histone variant control embryonic development in mice. - Antoine Molaro; Anna J Wood; Derek Janssens; Selina M Kindelay; Michael T Eickbush; Steven Wu; Priti Singh; Charles H Muller; Steven Henikoff; Harmit S Malik (PLoS Biology, 2020)
Histone variants expand chromatin functions in eukaryote genomes. H2A.B genes are testis-expressed short histone H2A variants that arose in placental mammals. Their biological functions remain largely unknown. To investigate their function, we generated a knockout (KO) model that disrupts all 3 H2A.B genes in mice. We show that H2A.B KO males have globally altered chromatin structure in postmeiotic germ cells. Yet, they do not show impaired spermatogenesis or testis function. Instead, we find that H2A.B plays a crucial role postfertilization. Crosses between H2A.B KO males and females yield embryos with lower viability and reduced size. Using a series of genetic crosses that separate parental and zygotic contributions, we show that the H2A.B status of both the father and mother, but not of the zygote, affects embryonic viability and growth during gestation. We conclude that H2A.B is a novel parental-effect gene, establishing a role for short H2A histone variants in mammalian development. We posit that parental antagonism over embryonic growth drove the origin and ongoing diversification of short histone H2A variants in placental mammals.